Monetary Policy and Commercial Banks Profitability in Nigeria - Iwedi, Marshal; James, Egileoniso Daniel (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
This study examines the impact of monetary policy on profitability of commercial banks in Nigeria over the period from 1988 to 2021. Data on credit to deposit ratio, return on asset, return on equity, Z-score, money supply, income per head, interest rate, interest spread, and inflation were obtained from the statistical bulletin of the Central Bank of Nigeria. Autoregressive distributed lag (ARDL) techniques were used to estimate the short and long-term dynamic equilibrium relationship between monetary policy and commercial banks' profitability in Nigeria. The analysis confirms mixed integration through unit root tests, which justifies the use of the ARDL approach for the four baseline models. The estimation results for these models provide evidence of a cointegrating relationship between monetary policy and commercial bank profitability in Nigeria, indicating that all the variables are bound in the long run. Among the indicators of commercial bank profitability, return on asset responds more quickly to changes in monetary policy, compared to return on equity, credit-deposit ratio, and Z-score. The long-term disequilibrium adjustment further supports the presence of a cointegrating relationship among these variables. The estimated level equations demonstrate that money supply and inflation have positive multiplier effects on the bank credit-deposit ratio in the long run. Based on these findings, the study strongly recommends increasing the Z-score of the Nigerian banking sector by reducing the standard deviation of return on asset. The volatility of ROA in the Nigerian banking system contributes to a low Z-score, therefore, bank management teams should strive to maintain relatively stable ROA over time. The government should work on reducing inflation, particularly inflation resulting from reckless spending of public funds, excessive quoting by public officers, and corruption-induced inflation. The interest spread is too wide, and any increase in this margin has a negative impact on return on asset and equity. Accordingly, the study suggests meaningfully shrinking the margin between lending rate and deposit rate, aiming for a one-digit margin. Banks can achieve this by simply reducing lending rates to single digits.